Europium incorporation dynamics and some physical investigations within ZnO sprayed thin films - YUMAK YAHŞİ, AYŞE (ELSEVIER SCI LTD, 2016)
Europium doped ZnO thin films were deposited on glass substrates using a simple mini spray technique at 460 degrees C. The structural properties of as-prepared thin films were characterized by X-ray diffraction (XRD). Both undoped and Eu-doped films show strong preferred c-axis orientation. The maximum value of the volume cells was obtained at 1% doping level. The texture coefficient (TC) of the films along (002) direction changes with the doping level due to Eu incorporation. The optical band gap calculated from transmittance and reflectance spectra show the effect of concentration on this energy. They equally outlined the direct gap absorption of these materials. Analysis of Urbach-Martienssen model parameters allows nano-scale explanations of the doping-related divergence of Urbach tailing evolution. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Zinc oxide; Europium doping; Optical properties; Single oscillator model; Urbach tails; Dielectric constant; COMPATIBILITY THEORY LCT; OPTICAL-PROPERTIES; SUBSTRATE-TEMPERATURE; ELECTRICAL-PROPERTIES; AL; ENERGY; PHOTOLUMINESCENCE; NANOCRYSTALS; LUMINESCENCE; PATTERNS